Keefektifan Penggunaan Media Pembelajaran Berbasis Game Edukasi Quizizz Terhadap Hasil Belajar Teknologi Perkantoran Siswa Kelas X SMK Ketintang Surabaya - Cahyani Amildah Citra; Brillian Rosy (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
This research aims to determine the effectiveness of the effectiveness of learning media based educational game quizizz on student outcomes office technology grade X SMK Ketintang Surabaya. This type of research is using quasi experimental design. The circuit was conducted on all class X OTKP 2 students as a control class and X OTKP 3 as an experimental class. Analytical techniques use homogeneity test, normality test, hypothesis test and gain score test. The results of the study expressed the Posttest value obtained by t-test of 2.154 with a signification of 0.036 and a value of 2.002 with a level of significance 0.005 which means signification (0.036) < 0.05 and t-test (2.154) > ttable (2.002).The result of Gain Score the Pretest and Posttest value is 3,212 with a signication 0,002 and the value ttable is 2,002 with signification 0,05.  So it can be concluded that the use of learning media based on Quizizz educational Game effectively improve student learning outcomes on the subject of office technology class X OTKP in SMK Ketintang Surabaya.